Transforming lignin into porous graphene via direct laser writing for solid-state supercapacitors. Issue 39 (23rd July 2019) - Mahmood, Faisal; Zhang, Chi; Xie, Yunchao; Stalla, David; Lin, Jian; Wan, Caixia
Abstract : Direct laser writing transforms alkaline lignin into porous graphene for solid-state supercapacitors with high electrochemical performance. Abstract : Cost-effective valorization of lignin into carbon-based electrode materials remains a challenge. Here we reported a facile and ultrafast laser writing technique to convert lignin into porous graphene as active electrode material for solid-state supercapacitors (SCs). During laser writing, alkaline lignin experienced graphitization. By controlling laser parameters such as power the porous structure and graphitization degree can be well modulated. Graphene obtained at 80% of laser power setting (LIG-80) had higher graphene quality and more porous structure than that obtained at the lower power levels ( i.e., 50%, 70%). TEM images revealed that LIG-80 had few-layer graphene structure with fringe-like patterns. LIG-80 proved to be an active electrode material for SCs with a specific capacitance as high as 25.44 mF cm −2 in a H2 SO4 /PVA gel electrolyte, which is comparable or even superior to SCs based on pristine LIG obtained from other carbon precursors. Taken together, our proposed technical route for lignin-based LIG and subsequent application in SCs would not only open a new avenue to lignin valorization, but also produce porous graphene from a renewable carbon precursor for energy storage applications.